The use of protection orders in response to adolescent family violence: mapping divergent Australian approaches and the merits of this criminal justice intervention - Thomas, Kate; Fitz-Gibbon, Kate; Maher, JaneMaree (Current issues in criminal justice, 2019)
Several Australian state and territory jurisdictions permit parents of adolescents using violence to be listed as affected persons on a family violence protection order (the notable exceptions being Queensland and Tasmania), however, as yet there is minimal understanding of whether this is an effective response to this complex form of family violence. In seeking to address this gap in current knowledge, this paper has two aims. It analyses Australian family violence legislation as it applies to protection orders in cases of adolescent family violence, revealing significant disparity in state and territory legislative frameworks. The article then draws from the findings of a recent Victorian study to provide insight into the use, impact and effectiveness of protection orders in responding to adolescent family violence from the perspective of those experiencing adolescent family violence and those charged with responding to it in service and legal settings. By highlighting the diversity in state and territory responses to adolescent family violence and using the Victorian case to question the efficacy of protection orders, this article contributes to knowledge about criminal justice system responses to adolescent family violence and supports the need for further systematic research about prevalence and effective social and criminal justice responses.